1997
DOI: 10.1200/jco.1997.15.2.723
|View full text |Cite
|
Sign up to set email alerts
|

Immunotoxin therapy of small-cell lung cancer: a phase I study of N901-blocked ricin.

Abstract: N901-bR is an immunotoxin with potential clinical activity in SCLC. N901-bR is well tolerated when given by 7-day continuous infusion at the dose of 30 microg/kg(LBW)/d. Neurologic and cardiac toxicity were acceptable when given to patients with refractory SCLC. A second study to evaluate this agent after induction chemoradiotherapy in both limited- and extensive-stage disease was started following completion of this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(30 citation statements)
references
References 22 publications
0
29
0
1
Order By: Relevance
“…The immunoconjugate N901-bR showed potent cytotoxicity against CD56 ϩ SCLC cells in preclinical studies. Importantly, in a Phase I study treating patients with relapsed SCLC, N901-bR was well tolerated with acceptable toxicity (48) and potential clinical activity. In addition, immunohistochemical staining of tissue samples from patients receiving infusion of N901-bR has demonstrated the selective binding of the immunotoxin to target tumor SCLC cells located in the BM and other tissues (48).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The immunoconjugate N901-bR showed potent cytotoxicity against CD56 ϩ SCLC cells in preclinical studies. Importantly, in a Phase I study treating patients with relapsed SCLC, N901-bR was well tolerated with acceptable toxicity (48) and potential clinical activity. In addition, immunohistochemical staining of tissue samples from patients receiving infusion of N901-bR has demonstrated the selective binding of the immunotoxin to target tumor SCLC cells located in the BM and other tissues (48).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, in a Phase I study treating patients with relapsed SCLC, N901-bR was well tolerated with acceptable toxicity (48) and potential clinical activity. In addition, immunohistochemical staining of tissue samples from patients receiving infusion of N901-bR has demonstrated the selective binding of the immunotoxin to target tumor SCLC cells located in the BM and other tissues (48). This study suggested that mAb N901 linked to a cytotoxic agent can recognize and target CD56 ϩ tumor cells in vivo, in particular in a setting of a disseminated human disease involving BM localization.…”
Section: Discussionmentioning
confidence: 99%
“…In a phase I study in 21 patients with relapsed or refractory SCLC, only one patient showed PR out of the 20 patients that have been evaluated. This trial was last reported in 1997 [130][131][132]. The phase II trial in nine SCLC patients was unsuccessful, since no objective response to N901-bR was observed.…”
Section: N901-brmentioning
confidence: 99%
“…The scFv described here may also be a useful reagent in such detection assays and is a starting point for future variants produced by genetic engineering techniques that have improved properties for clinical application. In particular, the design and production of immunotoxins based on this construct could have a significant clinical relevance (43,44). Although C219 is directed toward a cytoplasmic epitope, there are a number of efforts under way to direct compounds to the cytoplasm either by using translocation signals (e.g.…”
Section: Discussionmentioning
confidence: 99%